2010
DOI: 10.1002/ase.184
|View full text |Cite
|
Sign up to set email alerts
|

An audience response system may influence student performance on anatomy examination questions

Abstract: This study integrated an in-house audience response system (ARS) in the human anatomy course over two years to determine whether students performed better on high-stakes examinations following exposure to similar interactive questions in a large lecture format. Questions in an interactive ARS format were presented in lectures via PowerPoint presentations. Students who chose to participate in the anonymous ARS sessions submitted answers via their personal wireless devices (e.g., laptops, smartphones, PDAs, etc)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 16 publications
5
28
0
Order By: Relevance
“…Nonparticipation extends to another trend; a decline in the rate of participation over time. This decline was observed in both of this studies and has been reported to occur with practice quizzes ) and the use of other voluntary course resources whether it is an audience response system (Hoyt et al, 2010) or an online dissector (Mc Nulty et al, 2004). These declines may be the result of students discovering that a specific resource does not fit their learning style and/or increasing demands on their time as the course progresses (Smythe and Hughes, 2008).…”
Section: Discussionsupporting
confidence: 59%
“…Nonparticipation extends to another trend; a decline in the rate of participation over time. This decline was observed in both of this studies and has been reported to occur with practice quizzes ) and the use of other voluntary course resources whether it is an audience response system (Hoyt et al, 2010) or an online dissector (Mc Nulty et al, 2004). These declines may be the result of students discovering that a specific resource does not fit their learning style and/or increasing demands on their time as the course progresses (Smythe and Hughes, 2008).…”
Section: Discussionsupporting
confidence: 59%
“…A strategy to computerize an anatomy laboratory created more independent and proficient adult learners (Reeves et al, 2004). Audience response systems (ARS) enhanced the learning experience (Hoyt et al, 2010) and a two-year study showed a direct correlation between examination grades and the frequency of CAI use (McNulty et al, 2004). After medical school, technology enhanced simulation in training of healthcare providers is associated with large effects in knowledge and skill outcomes and even moderate ones for patient related outcomes (Cook et al, 2011).…”
Section: Computer Assisted Instruction (Cai)mentioning
confidence: 97%
“…A review of the literature suggested the benefits of implementing clickers in classrooms such as improving large classes' student engagement and academic performance [14][15][16]. Most of the current studies focus on the effectiveness of clickers [17][18][19] on summative results and students' engagement.…”
Section: Introductionmentioning
confidence: 99%